Sistem Reservasi Kunjungan Desa Wisata Berbasis Web Studi Kasus di Desa Wisata Lerep - Mustagfirin Mustagfirin; Dani Setiawan; Arif Rifan Rudiyanto (Universitas Wahid Hasyim, 2023)
The Tourist Village Visit Reservation System is a system that manages all information provided at a tourist destination. Lerep Tourism Village previously did not have a system that allowed data processing quickly and easily. The current reservation system is still manual, meaning that if prospective visitors want to enjoy the activities of the Lerep Tourism Village, they must come directly to the administration or make a reservation by telephone and the documentation of newly entered data and visit schedules has not been organized properly and quickly in this problem, researchers created a web-based information system developed using the waterfall method and supported by a MySQL database for data processing. With this information system, prospective visitors quickly report the visit schedule up to date. The end result is an online Lerep Tourism Village Visit reservation system.